ANTHROZOOLOGICAL APPROACH: MAN-ANIMAL CONFLICTS IN QUEPEM, GOA - RAO, KULKARNI RAJENDER; NIKITA, BODEKAR; SANKET, BORKAR; SIDHIKA, FERNANDES; SIYA, MALKARNEKAR; RAKHEE, MANGAONKAR; PRACHITA, SAWANT DESSAI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The life of humans and animals is always been intertwined, the ways that humans relate to and think about members of other species became the focus of systematic study in recent period. Anthrozoology is an exciting, rapidly growing field of scientific inquiry focussing on human’s individual and collective relationships with, and attitude towards animals. Widely inter disciplinary, anthrozoologists study a range of areas such as pet keeping, farming, animal research, conservation, zoo’s, animal in sports, companion animals and other related aspects. Anthrozoological inquiry include the psychological and biological underpinnings of attachments to pets, attitudes towards the use of animals, cross cultural similarities, differences in human animal relationships, sex differences in interaction with other species and the role of animals in art, religion, mythology, sport and literature. The major focus of anthrozoological research is the quantifying of the positive effect of human animal relationship on either party and study of their interactions. In the present investigation an attempt is made to understand the attitude of the Goan society towards domestication, species preference in domestication, Concern for their safety and Man animal conflicts.